2020
DOI: 10.21203/rs.3.rs-97641/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Analysis of Leaf Trait and Differentially Expressed Genes of Leaf Development in Eucommia ulmoides Oliver after Ultraviolet-B (UV-B) Radiation

Abstract: Background Eucommia ulmoides Oliver (EUO) has a great medicinal value in China. The using leaf model of Eucommia planting (ULMEP) is a promising approach to resolve the shortage of EUO resources. We focused on leaf responses and differentially expressed genes (DEGs) for transcriptome profiling after ultraviolet-B radiation (UV-B) in the east-north China. ResultsThe leaf traits were significantly affected after UV-B treatment, and the leaf area, leaf thickness and total leaf fresh/dry weight significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…At present, there is no direct study on the changes of metabolic pathways in sewage treatment under UV radiation, but related studies on plants have shown that UV radiation can change genes and affect metabolic pathways. Zhou et al (Zhou et al, 2020) found UV-C irradiation promoted the synthesis of phenols, avonoids and anthocyanins by up-regulating expressions of phenylalanine ammonia-lyase e, 4coumarate-CoA ligase, chalcone synthase, dihydro avonol 4-reductase and UDP-glucose: avonoid glucosyltransferase when transcriptomics and proteomics approaches were applied to investigate changes in peaches treated with UV-C. li et al (Li et al, 2020) found 1,826 up-regulated and 1,872 downregulated genes in the research of leaf responses and differentially expressed genes of Eucommia ulmoides Oliver for transcriptome pro ling after ultraviolet-B radiation (UV-B) in the east-north China. And Among them, the up-regulated unigenes were mainly participated in Signal transduction mechanisms, and Cell wall/membrane biogenesis by the KOG database, and up-regulated genes were analyzed in plant hormone signal transduction and phenylpropanoid metabolic pathways by KEGG pathway.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no direct study on the changes of metabolic pathways in sewage treatment under UV radiation, but related studies on plants have shown that UV radiation can change genes and affect metabolic pathways. Zhou et al (Zhou et al, 2020) found UV-C irradiation promoted the synthesis of phenols, avonoids and anthocyanins by up-regulating expressions of phenylalanine ammonia-lyase e, 4coumarate-CoA ligase, chalcone synthase, dihydro avonol 4-reductase and UDP-glucose: avonoid glucosyltransferase when transcriptomics and proteomics approaches were applied to investigate changes in peaches treated with UV-C. li et al (Li et al, 2020) found 1,826 up-regulated and 1,872 downregulated genes in the research of leaf responses and differentially expressed genes of Eucommia ulmoides Oliver for transcriptome pro ling after ultraviolet-B radiation (UV-B) in the east-north China. And Among them, the up-regulated unigenes were mainly participated in Signal transduction mechanisms, and Cell wall/membrane biogenesis by the KOG database, and up-regulated genes were analyzed in plant hormone signal transduction and phenylpropanoid metabolic pathways by KEGG pathway.…”
Section: Introductionmentioning
confidence: 99%